Puma response to the effects of fire and urbanization. Issue 2 (13th November 2015) - Jennings, Megan K.; Lewison, Rebecca L.; Vickers, T. Winston; Boyce, Walter M.
ABSTRACT: In southern California, wildfire and urbanization influence landscape condition and features. We explored the synergistic effects of these disturbances on puma ( Puma concolor ) movement and habitat preference in southern California, USA using a telemetry dataset of >40 individuals from 2001 to 2011. We examined post‐fire movement of tracked pumas to consider the relationship between habitat use and availability as animals used the landscape. We also explored puma response to burned areas to examine the influence of vegetation cover, time since fire, fire frequency, and the synergistic effects of urbanization on puma landscape use. We compare our results to those of others by using a complementary approach to evaluate how habitat relationships change with additional puma data and with consideration of the fire history of the landscape. Our analyses suggest that after fires, pumas use burned habitats opportunistically, responding to post‐fire changes in prey density. Additionally, time since fire and fire frequency were useful predictors of puma presence at the individual‐ and population‐level. Our puma habitat models showed a strong relationship between puma habitat use, vegetation, and human developments. Our analysis suggests that fire is an important landscape element to consider when evaluating puma habitat; pumas opportunistically used recently burned areas in the first few years after fire. We identified that pumas avoided grassland vegetation types and areas of sparse cover, suggesting that increasing fire frequency could affect puma habitat suitability and connectivity in the future. Fire frequencies in parts of southern California have already increased beyond the threshold to which the ecosystem is resilient, and if this trend continues across the region, suitable puma habitat may be lost through vegetation‐type conversion to homogenous non‐native annual grasslands, a habitat avoided by pumas during foraging and resting. We suggest monitoring responses to increasing fire frequency to assess how pumas and other carnivores will be affected by large‐scale changes that may pose a threat to landscape integrity and persistence of puma populations in southern California. © 2015 The Wildlife Society.